Comparison of three quality of life instruments in lymphatic filariasis: DLQI, WHODAS 2.0, and LFSQQ. - Cristina Thomas; Saravu R Narahari; Kuthaje S Bose; Kuthaje Vivekananda; Steven Nwe; Dennis P West; Mary Kwasny; Roopal V Kundu (PLoS Neglected Tropical Diseases, 2014)
Background The Global Program to Eliminate Lymphatic Filariasis aims to interrupt transmission of lymphatic filariasis and manage morbidity in people currently living with the disease. A component of morbidity management is improving health-related quality of life (HRQoL) in patients. Measurement of HRQoL in current management programs is varied because of the lack of a standard HRQoL tool for use in the lymphatic filariasis population. Methodology/principal findings In this study, the psychometric properties of three health status measures were compared when used in a group of lymphatic filariasis patients and healthy controls. The World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0), the Dermatology Life Quality Index (DLQI), and the Lymphatic Filariasis Quality of Life Questionnaire (LFSQQ) were administered to 36 stage II and stage III lymphatic filariasis subjects and 36 age and sex matched controls in Kerala, India. All three tools yielded missing value rates lower than 10%, suggesting high feasibility. Highest internal consistency was seen in the LFSQQ (α = 0.97). Discriminant validity analysis demonstrated that HRQoL was significantly lower in the LF group than in controls for the WHODAS 2.0, DLQI, and LFSQQ, but total HRQoL scores did not differ between stage II and stage III lymphedema subjects. The LFSQQ total score correlated most strongly with the WHODAS 2.0 (r = 0.91, p<0.001) and DLQI (r = 0.81, p<0.001). Conclusions/significance The WHODAS 2.0, DLQI, and LFSQQ demonstrate acceptable feasibility, internal consistency, discriminate validity, and construct validity. Based on our psychometric analyses, the LFSQQ performs the best and is recommended for use in the lymphatic filariasis population.